Repeated Interoceptive Exposure in Individuals With High and Low Anxiety Sensitivity. Issue 4 (July 2019) - Holtz, Katharina; Hamm, Alfons O.; Pané-Farré, Christiane A.
Interoceptive exposure is one component in cognitive behavioral therapy of panic disorder. The present investigation addressed changes in defensive mobilization during repeated interoceptive exposure using a standardized hyperventilation procedure. 26 high and 22 low anxiety sensitive persons (ASI, Peterson & Reiss, 1992) went through two guided hyperventilation and normoventilation procedures, spaced one week apart. Breathing parameters, startle response magnitudes and symptom reports were measured. All participants successfully adhered to the guided breathing procedures. Both groups comparably reported more symptoms during hyperventilation than normoventilation in both sessions. Only high-AS participants displayed potentiated startle magnitudes after the first hyperventilation vs. normoventilation. One week later, when the hyperventilation exercise was repeated, this potentiation was no longer present. Thus, high and low-AS groups no longer differed in their defensive mobilization to symptom provocation. Furthermore, the number of reported baseline symptoms also decreased from session one to session two in the high-AS group. While high-AS reported increased baseline anxiety symptoms in session 1, groups did not differ in session 2. Results indicate a reduction of defensive mobilization during repeated interoceptive exposure.